Beyond taxonomic diversity patterns – investigating how α and β components of macrophyte functional diversity respond to environmental gradients in lotic ecosystems of Greece - Stefanidis, Konstantinos; Oikonomou, Anthi; Dimitrellos, Georgios; Tsoukalas, Dionysios; Papastergiadou, Eva (Frontiers in Plant Science, 2023)
In addition to quantifying the taxonomic diversity of aquatic communities, understanding the patterns of alpha functional diversity (α-diversity) and exploring changes in functional dissimilarity (βdiversity) can improve our understanding on how ecosystems respond to environmental changes. In this study, we quantified functional alpha and beta diversity of aquatic plant communities from river sites in Greece and then, examined relationships with water quality parameters and hydromorphological factors. We assigned 6 traits (Ellenberg nutrients indicator, Ellenberg light indicator, growth form, leaf size, leaf type, fruit size) to a total of 36 hydrophyte species and calculated three indices of functional diversity (functional richness, functional dispersion and functional evenness). We also estimated the total β-functional diversity and its' main components, turnover and nestedness. To assess the effects of water quality (including physical and chemical variables) we used generalized additive models (GAM) for alpha functional diversity indices and generalized dissimilarity models (GDM) for beta functional diversity. We performed Kruskal-Wallis tests and permutational multivariate analysis of variance (PERMANOVA) to search for significant variations of αand βdiversity among the hydromorphological factors. Our results showed that macrophyte growth form and light preference were important trait characteristics that explained a large share of the total variance of functional composition. We also found relatively low taxonomic and functional richness, whereas taxonomic and functional dissimilarity were mostly attributed to species turnover, which expresses the changes in taxonomic and functional composition. We found significant relationships between functional dispersion and functional evenness with pH and oxygen saturation, whereas functional dissimilarity was driven only by geographic distance, although the GDM explained a small portion of the total variance. Functional richness, dispersion and evenness were significantly higher at systems with fine substrates and deep waters with low or high flow compared to systems with coarser substrates and riffle habitats. We also found significant variation in functional dissimilarity among the hydromorphological factors, although much of the total variance remained unexplained. Overall, our 2 This is a provisional file, not the final typeset article study highlights the importance of considering the functional diversity of aquatic plant communities within the frame of freshwater monitoring and conservation plans.